Acute coronary syndromes in chronic kidney disease patients: the good, the bad or the ugly?. (25th November 2020) - Saleiro, C; De Campos, D; Lopes, J; Teixeira, R; Sousa, J.P; Gomes, A.R.M; Puga, L; Costa, M; Goncalves, L
Abstract: Background: Patients with chronic kidney disease (CKD) are at increased risk of composite cardiovascular (CV) events and all-cause mortality. However, current aggressiveness of therapeutic strategies may minimize the course of the disease. Aim: To assess the prognostic impact of optimized medical treatment in a CKD population with acute coronary syndrome (ACS). Methods: 355 ACS patients admitted to a single coronary care with CKD who were discharged from hospital were included. Those with end-stage renal disease were excluded. Three groups were created based on the KDIGO classification: Group A (Stage 3A, eGFR [estimated glomerular filtration rate] 45–59mL/min/1.73 m 2 ) N=190; Group B (Stage 3B, eGFR 30–44mL/min/1.73 m 2 ) N=113; and Group C (Stage 3B, eGFR 15–29mL/min/1.73 m 2 ) N=52. The primary endpoint was long-term all-cause mortality. Kaplan-Meyer survival curves and Cox regression were done. The median of follow-up was 32 (IQ 15–70) months. Results: Groups were similar regarding demographics, CV risk factors, ACS type, heart failure diagnosis, left ventricular (LV) systolic function, peak troponin, multivessel disease, treatment option (PCI, CABG or OMT) and medical therapy at discharge. More advance renal failure patients had a higher prevalence of diabetes mellitus (DM), a lower haemoglobin, a higher NT-proBNP and were less likely to receive ACE inhibitors/angiotensin II antagonist at discharge. 170 patients met the primary outcome. Kaplan-Meyer curves showed decreased survival with worse renal function (Group A 68% vs Group B 57% vs Group C 37%, Log Rank P=0.006 – Figure 1). After adjustment for age, DM, haemoglobin, NT-proBNP, LV systolic function and ACE inhibitors/angiotensin II antagonist at discharge, eGFR was not associated with increased death (HR 1.00, 95% CI 0.98–1.01). In this model, only age (HR 1.04, 95% CI 1.01–1.07), haemoglobin (HR 0.86, 95% CI 0.979–0.94), Nt-proBNP (HR 1.00, 95% CI 1.00–1.00) and impaired LV function (LV ejection fraction 40–49%: HR 2.95, 95% CI 1.89–4.81; LV ejection fraction <40%: HR 2.15, 95% CI 1.44–3.21) remained associated with the outcome. Conclusion: The worse outcome attributed to CKD after an ACS seems to be related not the eGFR itself but to associated comorbidities such as age, anaemia, fluid overload and impaired LV function. The fact that some of these comorbidities may be altered by intensive therapy indicates that CKD patients should also be candidates to optimized medical treatment. Funding Acknowledgement: Type of funding source: None